2015
DOI: 10.1007/s10854-015-4252-0
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial microstructure, wettability and material properties of nickel (Ni) nanoparticle doped tin–bismuth–silver (Sn–Bi–Ag) solder on copper (Cu) substrate

Abstract: This paper investigates the influence of adding nickel (Ni) nanoparticles on the microstructure, wettability and material properties of Sn-35Bi-1Ag (wt%) based solders. Material properties such as elastic and shear moduli, stress/strain behavior and electrical resistivity of bulk composite solder were improved significantly in comparison to the corresponding properties of reference solder alloy. The elastic and shear moduli of composite solder increased about 16.8 and 19 % respectively, while the electrical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…The thickness of interfacial IMC layer (d) was measured by using the following Equation (1) the average thickness is used as the roughness measurement datum identified as a dotted line in Figure 3. The interface roughness of the IMC layer with a micro interface contour is characterized by its roughness (R), which can be estimated from Equation (2). Z i in Equation (2) presents the deviation of the peaks or troughs of the interface from the average thickness d of the IMC as shown in Figure 3.…”
Section: D=a/lmentioning
confidence: 99%
See 2 more Smart Citations
“…The thickness of interfacial IMC layer (d) was measured by using the following Equation (1) the average thickness is used as the roughness measurement datum identified as a dotted line in Figure 3. The interface roughness of the IMC layer with a micro interface contour is characterized by its roughness (R), which can be estimated from Equation (2). Z i in Equation (2) presents the deviation of the peaks or troughs of the interface from the average thickness d of the IMC as shown in Figure 3.…”
Section: D=a/lmentioning
confidence: 99%
“…The interface roughness of the IMC layer with a micro interface contour is characterized by its roughness (R), which can be estimated from Equation (2). Z i in Equation (2) presents the deviation of the peaks or troughs of the interface from the average thickness d of the IMC as shown in Figure 3. To reduce measurement error, five random measurement places were selected and the finally result was expressed as the average of these measurements.…”
Section: D=a/lmentioning
confidence: 99%
See 1 more Smart Citation
“…After adding Ni nanoparticles into SnBiAg solder, the Bi-rich phase and Ag 3 Sn IMC was refined because the formation of Ni-Sn IMCs could act as nucleation sites and inhibit the grain growth [55]. With the addition of 0.4 wt.% Ag nanoparticles, a mass of dispersed nano-Ag 3 Sn particles formed, which inhibited the grain growth and provided a refined microstructure [56].…”
Section: Microstructurementioning
confidence: 99%
“…Numerous studies [6][7][8] have already demonstrated that one solder with more refined microstructures and thinner interfacial intermetallic compound (IMC) layers usually has a better joint reliability. To achieve this, several research groups are focused on developing composite materials doped with different types of micro-and nano-scale metallic e.g., Ag [9], Ni [10], In [11], Al [12], Co [13]; ceramic e.g., TiO 2 , ZrO 2 , Al 2 O 3 , and TiO 2 etc. [9,[14][15][16] and rare earth (RE) elements [17][18][19].…”
Section: Introductionmentioning
confidence: 99%